Poziom akumulacji cynku, kadmu i ołowiu w wierzchniej warstwie gleb leśnych w sąsiedztwie Huty Cynku "Miasteczko śląskie" = The level of Zn, Cd and Pb accumulation in top layer of forest soil in the neighbourhood of metallurgic complex "Miasteczko śląskie" - Pająk, Marek; Jasik, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this paper was to determine the heavy metals (Zn, Pb, Cd) pollution in forest environment in Brynica district of Forest inspectorates Świerklaniec. Determination of their accumulation in top layer of soils horizon and forest litter. Samples of top layer of soils (0-20 cm) and forest litter were taken at 31 systematically located points on the 1500 x 1500 m grid in July 2008.
Keywords: zanieczyszczenie środowiska; gleba; metale ciężkie; pierwiastki śladowe; environment pollution; heavy metals; soils; trace elements